Sobrevivência, crescimento e parâmetros metabólitos teciduais em alevinos de jundiá Rhamdia quelen expostos a diferentes níveis de oxigênio dissolvido - Braun, Neiva (2005)
The objective of this study was to verify survival and growth of silver catfish (Rhamdia quelen) fingerlings in different concentrations of dissolved oxygen, as well as its effect on glycogen, glucose, and protein in the liver, kidney, and muscle and activity of the hepatic catalase. In the first experiment 10 fingerlings were used (2.23 ± 0.13 g) in each experimental unit (2 liters) for determination of the lethal concentration (LC-50) in 96 hours for dissolved oxygen. Fingerlings were exposed to 0.40 ± 0.05, 0.76 ± 0.07, 1.04 ± 0.14, and 1.68 ± 0.32 mg/L of dissolved oxygen (three replicates per treatment). In the second experiment 10 fingerlings (4.99 ± 0.18 g) were used for experimental unit (40 liters), and were exposed to 1.96 ± 0.08, 3.10 ± 0.10, 4.14 ± 0.09, 5.20 ± 0.07, and 6.16 ± 0.03 mg/L of dissolved oxygen (three replicates per treatment) for 30 days. LC50 was 0.52 mg/L (confidence interval 0.42 - 0.61). In the growth experiment positive correlation was observed between dissolved oxygen and standard length, weight, specific growth rate, and biomass, and negative correlation for food conversion and catalase. Levels of hepatic glycogen reduced with the increase of oxygen levels. Glucose and the lactate showed variable levels. In the muscular tissue, glicogen levels decreased with the increase of oxygen concentration and glucose and lactate presented variations in the different treatments. There was no significant difference among treatments in the renal glycogen levels, either protein levels of the studied tissues. The best oxygen level for development of silver catfish is above 4.3 mg/L of dissolved oxygen.